Decision Support System for the Level of Employee Salary Increase at PT. Salim Ivomas Pratama Tbk, using the Simple Additive Wheigting (SAW) Method - Catur Wahyuwidodo (International Journal of Basic and Applied Science, 2020)
Utilization of a decision support system using the Simple Additive Weighting (SAW) method is very helpful for managers in making decisions that are faster and more accurate. The basic concept of the SAW method is to find the weighted sum of the performance ratings on each alternative and on all attributes that require the normalization process of the decision matrix (X) to a scale that can be compared with all existing alternative ratings. This method was chosen because it is able to select the best alternative from a number of alternatives based on the specified criteria. The research was conducted by finding the weight value for each attribute and then ranking it to determine the optimal alternative.